2020
DOI: 10.1021/acsnano.0c05885
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Real-Time Pharmaceutical Evaluations of Near-Infrared II Fluorescent Nanomedicine Bound Polyethylene Glycol Ligands for Tumor Photothermal Ablation

Abstract: Pharmaceutical evaluations of nanomedicines are of great significance for their further launch into industry and clinic. Near-infrared (NIR) fluorescence imaging plays essential roles in preclinical drug development by providing important insights into the biodistributions of drugs in vivo with deep tissue penetration and high spatiotemporal resolution. However, NIR-II fluorescence imaging has rarely been exploited for in vivo real-time pharmaceutical evaluations of nanomedicine. Herein, we developed a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…FLI image: Reproduced with permission. [59] Copyright 2020, American Chemical Society. PTT image: Reproduced with permission.…”
Section: Construction Strategies Of Nir-ii Organic Nanotheranosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…FLI image: Reproduced with permission. [59] Copyright 2020, American Chemical Society. PTT image: Reproduced with permission.…”
Section: Construction Strategies Of Nir-ii Organic Nanotheranosticsmentioning
confidence: 99%
“…Li et al designed a new thiadiazolobenzotriazole (BTZ) acceptor as a NIR-II core to develop a NIR-II SM DTTB, which showed a high fluorescence QY of 13.4% (IR1061 as the reference with QY of 0.75% in DCM) and a large absorption coefficient of 4.9 × 10 4 L mol −1 cm −1 at 808 nm. [59] Three amphiphilic polymers with different lengths of PEG chains were used to encapsulate DTTB to form the nanomicelles of DTTB@PEG-1K, DTTB@PEG-3K, and DTTB@PEG-5K with different surface morphology. The three nanomicelles with similar size distribution exhibited an absorption and emission peak at 750 and 1050 nm, respectively.…”
Section: Multimodal Imaging-guided Pttmentioning
confidence: 99%
“…Apart from fluorescence emission in the visible region, CPs can extend their emission spectra into NIR region through D-A design, and thus were used in NIR imaging to improve the penetration depth and sensitivity of bioimaging in biological tissue and living animals. [39,52,53] Liu et al first reported a far-red/ NIR fluorescent CP PFBTDBT which consisted of fluorene and benzothiadiazole. After further fabrications, the PFBTDBT was prepared into a NIR nanoparticle with an emission maximum at 698nm, which offered an attractive fluorescence material for in vivo imaging.…”
Section: Multicolor and Nir Imagingmentioning
confidence: 99%
“…Benefitting from continuous improvement in the research of NIR‐II AFPs, the probes can effectively actualize superior tissue visualization, accurate disease diagnosis and available therapy. In recent years, more and more NIR‐II‐based therapeutic applications such as drug delivery and release, [107–111] imaging‐guided surgery [112–115] and imaging‐guided photothermal therapy (PTT) [116–119] have made remarkable progress and demonstrated their superior advantages in diseases therapy.…”
Section: Recent Advances In Nir‐ii‐based Therapeutic Applicationsmentioning
confidence: 99%
“…Furthermore, Liang's group reported a NIR‐II fluorescent probe that was successfully applied in visualization for metabolic behaviors and real‐time drug assessment of nanomedicine in vivo [111] . The acquired NIR‐II probe was a D‐A‐D conjugated oligomer, which was constructed by using thiadiazolobenzotriazole (BTZ) as the NIR‐II acceptor core and then anchoring the oligomer into polyethylene glycolated micelles.…”
Section: Recent Advances In Nir‐ii‐based Therapeutic Applicationsmentioning
confidence: 99%